"And of course our major contribution remains to run a decent business." Making sense of Shell's sense-making in Nigeria during the 1990s. (1st February 2017) - Hofferberth, Matthias
Abstract: The intellectual engagement with multinational enterprises in International Relations has found a new home within the narratives of global governance and corporate social responsibility. Both narratives seem to agree that the role of business has changed as state capacities to provide governance assumingly have diminished and, based on broader social and political responsibilities, enterprises began to participate more actively in the provision of collective goods. Increased participation alone, however, does not reveal how corporate actors define and make sense of their responsibilities and their roles within global governance. In fact, focusing on corporate responsibilities and corporate governance contributions does not consider enterprises as actors in their own right who actively interpret and respond to changes in their normative environments. To fill this gap, the article proposes a framework that conceptualizes corporate agency as inherently social and creative. This framework, which can be applied to different contexts, is illustrated by reconstructing interpretative frames and self-understandings advanced by Shell in response to its crisis in Nigeria during the 1990s. Based on this reconstruction, Shell failed to develop and communicate a clear understanding of its social responsibilities, and its overall integration into global governance is likely to remain an ambiguous process in which uncertainty and indeterminacy prevail.